Thirty Years of Information Research - Crystal Fulton; Wout Dillen (Information Research: An International Electronic Journal)
April 2025 marked the 30th year anniversary of Information Research. To celebrate this occasion, the current issue of the journal is a special issue, filled with short contributions commemorating the impact the journal and its founder have had on the research field and its practitioners.